"Expecting children to be dragons" in an east asian context: Parental expectations of children choosing a career in the public sector. Issue 2 (3rd April 2023) - Chen, Chung-an; Xu, Chengwei; Chen, Don-Yun
ABSTRACT: In East Asia, where a culture of submission to authority dominates, parental expectations significantly influence children's career choices. A recent empirical study conducted in Taiwan shows that children are more inclined to pursue a public service career when influenced by their parents' expectations. The present study asks two questions: why do parents in East Asia expect children to secure a career in public service? Is it a result of social pressure, parents' own values, their socio-economic status, or all of these possible reasons? The present study uses data collected in Taiwan to answer these questions. Our findings broaden the current knowledge base of parental socialisation and its effect on children's preference for public sector careers.